Influência da duloxetina e amitriptilina na farmacocinética e efeito biológico da pregabalina para tratamento da dor crônica em animais - Rodrigues, Rafaela Figueiredo (2016)
Pain is an unpleasant sensory and emotional experience that occurs in different degrees of intensity, which can result in nerve stimulation due to injury, illness or emotional disturbance. The pain can be classified temporally as acute and chronic pain, including neuropathic. Neuropathic pain is more complex due to its resistance to common analgesics. This way, the Ministry of Health advocated for treating this type of pain, in humans, as first choices: pregabalin, duloxetine and amitriptyline. The aim of this study is to analyze the pharmacokinetics of pregabalin and biological effect of monotherapies and their combinations in animals and find what medication profile is more effective. The evaluation of the biologic effect was carried out in six groups: Wistar (220-250g, n = 12 for each group), who used pregabalin (PREG) (10mg/kg P.O); pregabalin (10mg/kg P.O) + amitriptyline (1 mg/kg P.O) (AMITRIP+PREG); pregabalin (10mg/kg P.O) + duloxetine (30 mg/kg P.O) (PREG+DULOX); amitriptyline (1mg/kg P.O) (AMITRIP); duloxetine (30 mg/kg P.O) (DULOX) and vehicle (pure water V.O) (VEH). The model for chronic neuropathic pain was induced by chonic constriction of the sciatic nerve and assessment of nociception was realized by von Frey hair test. Pregabalin pharmacokinetics was evaluated as monotherapy or combination at the same doses described above (n = 6 profiles per treatment). Blood was collected from 0-24h and the plasma used for chromatographic analysis. After sample preparation, pregabalin was analyzed by ultra-efficiency liquid chromatography coupled to mass spectrometry. For detection and quantification of pregabalin and diazepam (internal standard) were used m/z transitions 158.00> 140.80; 158.00> 123.00; 158.00> 95.20 and 285.00> 154.05; 285.00> 192.90; 285> 222.10 respectively. The developed method was validated according to RDC 27/2012 and was linear, precise and accurate. To evaluate biological effect and kinetic disposition specific statistical tests were performed. The results showed that the groups operated PREG, PREG+AMITRIP and PREG+DULOX showed better analgesic effect compared to VEH group. When compared to PREG, only the PREG+AMITRIP group was statistically different from the PREG group, presenting prolonged and more effective results. Monotherapy adjuvants, AMITRIP and DULOX showed no antinociceptive or hypoalgesic effect. The kinetic disposition of PREG was changed in PREG+AMITRIP association with reduction of apparent total clearance and consequently increase in bioavailability, this finding could be associated with prolongation of the biological effect of the association between PREG + AMITRIP.